Pengaruh Perkembangan Usaha Mikro Kecil dan Menengah Terhadap Pertumbuhan Ekonomi di ASEAN 4 - Yusrin Fauziah (Universitas Jember, 2021)
ASEAN is an organization in the Southeast Asian region which has ten member countries. Among the ten ASEAN member countries, there are four countries that have the same characteristics, namely Indonesia, Malaysia, the Philippines and Thailand. The four countries are developing countries with low to medium income, where the economy is supported by Micro, Small and Medium Enterprises (MSMEs). This study aims to see the effect of the number of workers, the value of exports and the value of MSME capital loans on economic growth in ASEAN 4. The MSMEs studied are MSMEs in four ASEAN countries (Indonesia, Malaysia, the Philippines and Thailand) since 2009-2018. The analytical tool used is multiple linear regression using panel data by performing statistical tests (F test, t test and R2 test) and classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). Data analysis shows that the number of workers and the value of MSME capital loans have a positive and significant effect on economic growth in ASEAN 4. Meanwhile, the export value of MSMEs has a positive but not significant effect on economic growth in ASEAN 4. Keywords: MSMEs, Employment, Exports, Capital Loans and Economic Growth.